2020
DOI: 10.5194/egusphere-egu2020-4096
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil moisture decline following the plantation of Robinia pseudoacacia forests: Evidence from the Loess Plateau

Abstract: <p>Soil moisture is the foundation of ecosystem sustainability in arid and semi-arid regions, and the spatial–temporal details of soil moisture dynamics of afforested areas can benefit for land use management in watershortage regions such as the Loess Plateau of China. In this study, spatial–temporal variations in soil moisture under Robinia pseudoacacia plantations on the Loess Plateau were analyzed. A total of 147 observations of soil moisture content (SMC) data to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…Ren et al () also compared the effect of afforestation and natural revegetation on soil moisture and suggested that afforestation is the better option for the Loess Plateau only in areas with adequate annual rainfalls. Liang et al () analyzed spatial–temporal variations in soil moisture following the plantation of R. pseudoacacia forests on the Loess Plateau and suggested that afforestation should be avoided in areas where the local total precipitation is insufficient for replenishing the soil moisture. Many vegetation recovery activities, such as planting nonnative trees that consume a large amount of water in dry areas and indiscriminately increasing planting density (Wang & Shao, ) in the process of vegetation construction, have been inappropriate and resulted in a sharp decline in SMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ren et al () also compared the effect of afforestation and natural revegetation on soil moisture and suggested that afforestation is the better option for the Loess Plateau only in areas with adequate annual rainfalls. Liang et al () analyzed spatial–temporal variations in soil moisture following the plantation of R. pseudoacacia forests on the Loess Plateau and suggested that afforestation should be avoided in areas where the local total precipitation is insufficient for replenishing the soil moisture. Many vegetation recovery activities, such as planting nonnative trees that consume a large amount of water in dry areas and indiscriminately increasing planting density (Wang & Shao, ) in the process of vegetation construction, have been inappropriate and resulted in a sharp decline in SMC.…”
Section: Discussionmentioning
confidence: 99%
“…Coupled with the low precipitation, high evaporation, and unsupplied groundwater in the Loess Plateau (Yang et al, ), the soil moisture in this region is insufficient to meet the requirements of vegetation growth. Accordingly, it is vital to select vegetation types based on theoretically matching plant characteristics to the climate conditions and soil properties of certain places (Chen, Shang, Qian, Jing, & Liu, ), and local tree species with a lower demand for water resources should be considered an optimal choice for further afforestation of the Loess Plateau (Liang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another concern is the decrease of water yield, although due to the shrinkage of cropland area by GGP project, the demand for agricultural water use had decreased at the same time. Liang et al (2018) reported a decline of soil moisture after GGP imeplementation, forest has lower moisture content among cropland and grassland, while revegetation on the Loess Plateau is considered as a main driver for the moisture decrease. Clearly, forest expansion had brought more pressure on water supply than grassland on the Loess Plateau with an average annual precipitation from 250 mm ~ mm.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that black locust and understory species exerted favourable ecological effects in the regions with annual precipitation of more than 500 mm (Jin et al, ). However, in regions with insufficient precipitation, large area degradation and plant mortality occurred under black locust plantations due to severe desiccation (Liang et al, ). Besides, attention should be given to the management of reconstructed vegetation.…”
Section: Discussionmentioning
confidence: 99%